ANATOMIC OBSERVATIONS OF THE CORONARY SINUS IN THE DOG (CANIS-FAMILIARIS) - Piffer, C. R.; Piffer, MIS; Santi, F. P.; Dayoub, MCO (Blackwell Wissenschafts Verlag Gmbh, 1994)
The coronary sinus was investigated in 34 normal adult dogs, in order to verify its formation, tributaries, length and the valves, as well as the relationship of the venous walls to the epicardium and to the myocardium. The valve of the coronary sinus was observed in only 4 cases (1.7 %). In 30 cases (98.3 %) the ostium of the coronary sinus was lacking a valve. The valve of Vieussens double, was found at the level of the transition between the great cardiac vein and the coronary sinus, as well as others parietal venous valves. A comparison with the human pattern was made, particularly regarding the action of the valve of the coronary sinus and the formation of the sinus.